SOCIAL PROTEST MOVEMENT ISLAMIC LAW PERSPECTIVE (Critical Study of the Protest Phenomenon in Indonesia) - Abbas, Abdul Harris; Aidid, Hasyim; Pabbabari, Musafir; Marilang, Marilang (Jurnal Diskursus Islam, 2021)
This study formulates three problems which include: (1) The principles of the social protest movement from the perspective of Islamic law; (2) Methods and techniques for conducting demonstrations from the perspective of Islamic law; (3) The social impact of demonstrations in Indonesia from the perspective of Islamic law. This study uses a qualitative method (descriptive-analytic). Based on the data source is library research (library research). The approach used is the sociological approach of Islamic law and the siyasah fiqh approach. In the perspective of scientific studies, these two approaches are used to understand the phenomenon of demonstrations in Indonesia based on legal arguments contained in the Qur’an and Hadith, the opinions of fuqaha’ and opinions that develop (ijitahad) at a time in life. Muslims. Meanwhile, from a methodological perspective, these two approaches are used to provide an interpretation of the methodology of Islamic law on the concept and practice of demonstrations based on social movement theory and Islamic political theory. The results of this study found that: The principles of the Islamic social protest movement are built on the doctrine of rights and obligations between the people and the rulers in an Islamic state which include: the principle of hisbah; The principle of freedom of expression; The principle of deliberation; and constitutional principles. Based on the method of carrying out the demonstration, there are 2 methods, namely the exclusive method and the inclusive method. Based on the technique of holding demonstrations, there are 3 levels, namely: (1) demonstrations with the ability and strength of the masses; (2) demonstration with verbal ability and strength; (3) protest with the ability of the heart. Through the istislahi approach, that Islamic law strongly condemns all demonstration activities that cause harm to religion, soul, mind, descendants and property. On the other hand, he strongly supports all demonstration activities that uphold the five maintenances (Maqasid al-khamsah). That demonstrations are not at all motivated by passion or personal tendencies, let alone to cause damage to the earth. It is an obligation not just an appeal for those who can afford it. The law is fardu kifayah. Turning away from that obligation is the same as carrying oneself That demonstrations are not at all motivated by passion or personal tendencies, let alone to cause damage to the earth. It is an obligation not just an appeal for those who can afford it. The law is fardu kifayah. Turning away from that obligation is the same as carrying oneself That demonstrations are not at all motivated by passion or personal tendencies, let alone to cause damage to the earth. It is an obligation not just an appeal for those who can afford it. The law is fardu kifayah. Turning away from that obligation is the same as carrying oneself.